A Foundation for Behavioral Economics - Cohen, Jessica L; Dickens, William T (American Economic Review, 2002)
The core theory of behavior in Economics, which structures inquiry and provides a framework for empirical analysis, is largely responsible for the success of the discipline. Behavioral Economics (BE) challenges this theory, but has failed to provide a coherent alternative. Consequently the influence of BE has been limited. In what follows we argue that Evolutionary Psychology (EP), suitably adapted, can provide at least a partial foundation for BE. Its methods offer a way of generating theories of the origins of anomalous behaviors and of testing those theories. I. Behavioral Economics BE has been most successful in documenting failures of the rational actor model (e.g. failures of expected utility theory, irrational cooperation, and time inconsistent preferences). However, attempts to incorporate these observations into theory have been ad hoc: either an anomalous behavior is induced by modifying the utility function or the behavior is simply assumed and implications derived. The lack of theoretical foundations causes a number of problems for BE. First, empirical analysis can show the inadequacy of mainstream theory, but it does little to help develop alternatives. Second, without a